Front Cover. Issue 5 (19th April 2020) - Tu, Chaofeng; Wang, Ying; Nie, Hongchuan; Meng, Lanlan; Wang, Weili; Li, Yong; Li, Dongyan; Zhang, Huan; Lu, Guangxiu; Lin, Ge; Tan, Yue‐Qiu; Du, Juan
Abstract: The cover image is based on the Short Report An M1AP homozygous splice‐site mutation associated with severe oligozoospermia in a consanguineous family by Chaofeng Tu and Ying Wang et al., https://doi.org/10.1111/cge.13712 . Abstract : The cover image is based on the Short Report An M1AP homozygous splice‐site mutation associated with severe oligozoospermia in a consanguineous family by Chaofeng Tu and Ying Wang et al., https://doi.org/10.1111/cge.13712 .